Evaluación de la sustitución de productos auxiliares en el proceso de teñido de poliamida a nivel laboratorio en Protela S.A. (2020)
Protela S.A is a Colombian company with more than half decade of experience in the textile sector, with presence in several Latin American and Central American countries. Nowadays, the company works on improving its dyeing processes for having better quality standards to be able to offer competitive prices and being recognized in the textile sector. For this reason,an improvement proposal was presented and this consists in replacing the auxiliary products used in the polyamide dyeing process. To carry out the evaluation of the proposal, it was determined to work with the 5 most critical and demanded shades in the company in two types of fiber with different polyamide composition. It was evident that it was possible to replace several auxiliary products such as detergents, lubricants, antifoam, fixers, equalizers, among others, for only four auxiliary products. This process resulted in a saving of more than 10% in the formula cost of 7 tones and in the case of the cost of services, considerable savings